2004
DOI: 10.1097/00005537-200405000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Acute Otitis Externa: Efficacy and Tolerability of N‐Chlorotaurine, a Novel Endogenous Antiseptic Agent

Abstract: NCT appears to be well tolerated and more effective than the therapy using antibiotic component drops. Because of its endogenous nature and its higher efficacy, NCT appears to be a good choice for topical treatment of acute otitis externa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 24 publications
1
56
0
Order By: Relevance
“…This is in accordance with its oxidative mechanism of action (5,21) and with its efficacy in treatment of infections of different body sites in humans (for a review, see reference 5). For instance, successful application was demonstrated in purulently coated crural ulcerations and in external otitis in humans (22,23). Based on these findings, we speculate that the substance could be effective also for irrigation of orthopedic joint implants in case of infection or for prophylaxis of infections, supported by the following arguments.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This is in accordance with its oxidative mechanism of action (5,21) and with its efficacy in treatment of infections of different body sites in humans (for a review, see reference 5). For instance, successful application was demonstrated in purulently coated crural ulcerations and in external otitis in humans (22,23). Based on these findings, we speculate that the substance could be effective also for irrigation of orthopedic joint implants in case of infection or for prophylaxis of infections, supported by the following arguments.…”
Section: Discussionmentioning
confidence: 60%
“…This can be of advantage compared with highly reactive oxidants that cause side effects at higher dosages (21). Accordingly, NCT was shown to be effective in topical therapy of infections where biofilms play a role, for instance, purulently coated crural ulcerations and external otitis in humans (22,23) and joint infections in mice (7).…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable enhancement of the killing of molds (and of bacteria and protozoa) by the addition of NH 4 Cl to NCT known from previous studies (21,23,36) was also confirmed to a similar extent against Scedosporium. Due to the more rapid killing of microorganisms in body fluids and exudates, and due to the successful therapeutic application of NCT in humans and animals (14,15,21,23,37,38), we are convinced that this effect plays a role in vivo. It is explained by the formation of monochloramine (NH 2 Cl) in equilibrium with NCT (36,39).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the oxidative mechanism of action, NCT has typical broad-spectrum microbicidal activity against bacteria, viruses, fungi, and protozoa (12). Phase II clinical studies in conjunctivitis (13), external otitis (14), crural ulcers (15), and in the oral cavity (16) have already demonstrated its tolerability and therapeutic efficacy, and further applications are being investigated, e.g., via inhalation (17,18).…”
mentioning
confidence: 99%
“…HOCl solutions are still of interest, as can be derived from a recent study on the treatment of chronic venous leg ulcers (11). A completely new anti-infective concept was the introduction of a chloramine in the form of the natural compound N-chlorotaurine (NCT), which was successfully used in several clinical studies (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In a comparative trial on chronic leg ulcers, NCT showed the same efficacy as chloramine T but induced significantly less pain (17).…”
Section: Active Halogen Compoundsmentioning
confidence: 99%